Thermal conductivity of donor-doped GaN measured with 3ω and stationary methods - Churiukova, O.; Jeżowski, A.; Stachowiak, P.; Mucha, J.; Litwick, Z.; Perlin, P.; Susk, T. (Физика низких температур, 2015)
The thermal conductivity of three single crystal samples of n-type gallium nitride with electron densities of 4.0⋅10¹⁶, 2.6⋅10¹⁸, and 1.1⋅10²⁰ cm⁻³ has been determined in the temperature range 4–320 K. The measurements were carried out within the ab plane using the stationary method. The thermal conductivity depends strongly on the donor concentration. The analysis within the Callaway approach and the Debye model shows a significant influence of phonon–electron scattering on the thermal conductivity of the samples. In addition, some preliminary results obtained along the c axes of GaN layered samples are presented. The latter measurements have been carried out using the 3ω method.